2017
DOI: 10.1371/journal.pone.0169316
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Quality of Reporting of Observational Studies in Otorhinolaryngology - Based on the STROBE Statement

Abstract: BackgroundObservational studies are the most frequently published studies in literature. When randomized controlled trials cannot be conducted because of ethical or practical considerations, an observational study design is the first choice. The STROBE Statement (STrengthening the Reporting of OBservational studies in Epidemiology) was developed to provide guidance on how to adequately report observational studies.ObjectivesThe objectives were 1) to evaluate the quality of reporting of observational studies of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
24
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 36 publications
4
24
1
Order By: Relevance
“…Our study, similar to other studies ( 20 ), showed that the articles published in PubMed/ISI indexed journals were significantly more conformed to the statement. Yet, in our study and other studies ( 19 , 20 ), the conformity was not satisfactory even in the articles published in PubMed/ISI indexed journals. Therefore, improving the quality of all articles, including those published in PubMed/ISI indexed journals is necessary.…”
Section: Discussioncontrasting
confidence: 96%
See 1 more Smart Citation
“…Our study, similar to other studies ( 20 ), showed that the articles published in PubMed/ISI indexed journals were significantly more conformed to the statement. Yet, in our study and other studies ( 19 , 20 ), the conformity was not satisfactory even in the articles published in PubMed/ISI indexed journals. Therefore, improving the quality of all articles, including those published in PubMed/ISI indexed journals is necessary.…”
Section: Discussioncontrasting
confidence: 96%
“…Furthermore, the analyses of subgroups and interactions and sensitivity analyses should be reported to display potential interaction between risk factors, and to estimate the probable range of variation in outcome. However, in our study, similar to other studies ( 3 , 7 , 15 , 17 , 19 ), only few articles reported the analyses.…”
Section: Discussionsupporting
confidence: 86%
“…Thus, it is expected that the quality of reporting of such studies is poorer than that reported in the present survey, although the results of the present study indicate that even this quality is not sufficient. To our knowledge, this study is the first to assess the quality of reporting of observational studies in occupational medicine and health literature; however, similar work has been performed in other disciplines; for example, Hendriksma et al [ 7 ]. in 2016 con-ducted a similar study to evaluate the quality of reporting of observational studies in otorhinolaryngology based on the STROBE statement.…”
Section: Main Textmentioning
confidence: 99%
“…using “The Strengthening the Reporting of Observational Studies in Epidemiology” (STROBE) 11 checklist adherence percentage, when applicable, with a higher percentage indicating a better study quality. 12 Among available risk of bias tools, the STROBE checklist was selected in accordance to previous ORL literature, as it is a 23-item document with the aim of strengthening the quality of reporting in observational studies. 12 When inter-rater agreement could not be reached, the first Author (E.M.C.T.)…”
Section: Methodsmentioning
confidence: 99%